2015
DOI: 10.1063/1.4908060
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the van der Waals interaction in the dissociation dynamics of N2 on W(110) from first principles

Abstract: Calculation of the structure, potential energy surface, vibrational dynamics, and electric dipole properties for the Xe:HI van der Waals complex J. Chem. Phys. 134, 174302 (2011) ] exchange-correlation functionals were unable to fully describe the dependence of the initial sticking coefficient on the molecular beam incidence conditions as found in experiments. N 2 dissociation on W(110) was shown to be very sensitive not only to short molecule-surface distances but also to large distances where the vdW interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 76 publications
3
32
0
Order By: Relevance
“…For the vdW-DF functional, the molecular adsorption energies calculated are very similar to the PBE results. Moreover previous static surface AIMD simulations performed by Martin-Gondre et al 17 showed an underestimation of the experimental reaction probability using this functional. Therefore in this work we focus on the more promising vdW-DF2 functional.…”
Section: A Static Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the vdW-DF functional, the molecular adsorption energies calculated are very similar to the PBE results. Moreover previous static surface AIMD simulations performed by Martin-Gondre et al 17 showed an underestimation of the experimental reaction probability using this functional. Therefore in this work we focus on the more promising vdW-DF2 functional.…”
Section: A Static Resultsmentioning
confidence: 99%
“…There is experimental 18,41 and theoretical 10,11,15,17 evidence for the existence of molecular adsorption states of N 2 on W(110). The associated configurations are believed to be relevant to the indirect dissociation mechanism in which the molecule remains trapped near the surface before dissociating.…”
Section: A Static Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a very recent study [29], the dissociation of N 2 on W(110) has been investigated using density functionals in which the correlation has been corrected to account for dispersion interactions [30,31]. The authors have shown that some of these density functionals better describe properties such as adsorption energy and barriers for dissociation and desorption from the adsorption configuration that they have determined.…”
Section: Introductionmentioning
confidence: 99%